Knowledge of Cotton Growers in the Recommended Package of Practices of Cotton Cultivation - Sangeetha, V.; Prasad, S.V.; Venkatesh, (Indian Journal of Extension Education, 2009)
From the study it was found that majority of the respondents had medium levels of knowledge on recommended package of practices of cotton. The correlation analysis revealed that independent varibale, namely age, education, farming experience, contact with extension agency, mass media exposure, scientific orientation, risk preference, economic motivation, management orientation, achievement motivation, innovativeness and training undergone had positive and significant relationship with knowledge level of recommended package of practices of cotton.